Genetic therapies for RNA mis-splicing diseases. - Hammond, S; Wood, M (2011)
RNA mis-splicing diseases account for up to 15% of all inherited diseases, ranging from neurological to myogenic and metabolic disorders. With greatly increased genomic sequencing being performed for individual patients, the number of known mutations affecting splicing has risen to 50-60% of all disease-causing mutations. During the past 10years, genetic therapy directed toward correction of RNA mis-splicing in disease has progressed from theoretical work in cultured cells to promising clinical trials. In this review, we discuss the use of antisense oligonucleotides to modify splicing as well as the principles and latest work in bifunctional RNA, trans-splicing and modification of U1 and U7 snRNA to target splice sites. The success of clinical trials for modifying splicing to treat Duchenne muscular dystrophy opens the door for the use of splicing modification for most of the mis-splicing diseases.